2017
DOI: 10.1093/heapol/czx087
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go?: consistency and switching of delivery locations among new mothers in 39 Sub-Saharan African and South/Southeast Asian countries

Abstract: The objective of this article is to assess the extent and determinants of switching delivery location between women’s first and second deliveries. We used Demographic and Health Survey data from 39 low- and middle-income countries on delivery locations from >30 000 women who had their first two deliveries in the 5-year survey recall period. Each delivery was characterized as occurring at home or in a health facility, facilities were classified as public- or private-sector. The extent of switching was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 23 publications
5
36
1
Order By: Relevance
“…However, studies which adjust for parity mainly conclude that older age at motherhood is associated with increased odds of facility-based delivery. 10 16 Despite this, some reviews show inconsistent results, 7 no effect of age 11 or decreased use with age unless the woman was younger than 18. 5 Older motherhood is associated with wealth, education, marriage, wanted pregnancies, 7 multiple births, known health problems and complications of labour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies which adjust for parity mainly conclude that older age at motherhood is associated with increased odds of facility-based delivery. 10 16 Despite this, some reviews show inconsistent results, 7 no effect of age 11 or decreased use with age unless the woman was younger than 18. 5 Older motherhood is associated with wealth, education, marriage, wanted pregnancies, 7 multiple births, known health problems and complications of labour.…”
Section: Introductionmentioning
confidence: 99%
“…21 Additionally, the experience in the first birth may determine the future health-seeking behaviours of that mother. 10 …”
Section: Introductionmentioning
confidence: 99%
“…The reviewed pieces of literature reported inconsistent findings on the correlation between age and maternal service utilization; some show no effect [44], or older age at motherhood is associated with increased odds of maternity service use [45]. Our finding revealed that younger age at motherhood (between 15-24 years) was associated with increased odds of utilizing four or more ANC visits and facility-based delivery than older age women.…”
Section: Discussionmentioning
confidence: 49%
“…While this was not a pre‐specified focus of the research, given the background of overall high facility utilisation, this group emerged as an important subpopulation that is at greater risk for home delivery and potentially poor outcomes. For example, a recent study in 39 LMIC found that among women who had their first delivery at home, fewer than 12% switched to a facility for the second delivery . In our study population, the effect of the QI intervention was much stronger among these women, suggesting that their choice to remain home in the past may have been due to lack of high‐quality facility options nearby.…”
Section: Discussionmentioning
confidence: 64%
“…It is noticeable that the intervention did not have an effect on women whose prior delivery was at a health facility. This finding would be unsurprising if the default for these women was to deliver in a health facility – in the same study discussed above, nearly 80% of women who previously delivered in a facility used a facility for their second delivery .…”
Section: Discussionmentioning
confidence: 91%